Upaya Pencegahan Kekerasan Terhadap Anak - Rahma Apriliza Hasibuan; Syarifah Balqis; Octriliyanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Preventing violence against children is a global issue that requires serious attention from various stakeholders. This article discusses various prevention efforts undertaken in different countries to reduce incidents of violence against children. Approaches include educating and socializing communities, improving child protection systems, and enforcing stricter laws against perpetrators of violence. Case studies from several countries indicate that early education on children's rights and violence prevention, both in schools and within communities, is effective in changing behavior and raising awareness. Furthermore, collaboration between governments, NGOs, and the private sector is necessary to create safer environments for children. Despite numerous challenges, these efforts represent crucial initial steps in protecting children's rights and fostering a society more attentive to children's well-being